Determinants on service quality that affecting customer satisfaction in bumiputera printing industry / Siti Nur Fakhira Ismail - Ismail, Siti Nur Fakhira (2014)
The important issue of this research is to determine on service quality that effecting customer satisfaction in bumiputera printing industry. That means is there any relationship between all the independent variable with the dependent variable. Basically this research focus more on the bumiputera printing company in Pasir Gudang, Johor area. A framework was developed and tested whereby customer satisfaction is influenced by four element of service quality which is reliability, responsiveness, assurance and emphaty. There are several problem with bumiputera printing company, when government change their policy which is printing industries in Malaysia will become private sectors, it was give a big impact to bumiputera printing company. From this problem, it become a question to bumiputera printing company it is they also can satisfy their customer and whether they also can compete with other competitor among the same industry such as chinese printing company. The research is being focus to 70 and randomly chosen respondent as the data sampling in order to identify whether the services quality element has a relationship towards customer satisfaction. The findings and analysis were based on the data obtained from questionnaires. The analysis of findings involved the used of Cronbach Alpha in order to measure the reliability of data and descriptive statistics that consist of frequency distributions. Other than that, the correlation was used to see if there any significance differences in the means for all variables of interest. F- statistics has been carried out in order to determine whether there is a significant different between each individual selected demographic factors. Lastly for the findings of this research are useful to determine on service quality that affecting customer’s satisfaction in bumiputera printing industry.